Trends and patterns of head-and-neck cancer among a cohort of bidi smokers: A clinical study - Juhi Gupta; Md Asadullah; Sarah Mariam; Vipul Jain; Pradhuman Verma; Neha Agarwal (Wolters Kluwer Medknow Publications, 2022)
Background: In India, bidi smoking is prevalent among people of low socioeconomic status as it is cheaper than a cigarette. Aim: The aim of the current study was to analyze the pattern of distribution of oral and oropharyngeal cancer in bidi smokers in the Western Uttar Pradesh population. Materials and Methods: This unicentric cross-sectional study was conducted on patients having an exclusive habit of bidi smoking in the tertiary health care center from March 2019 to February 2022. Five hundred and eighty-five patients diagnosed with oropharyngeal or oral cancer, who were willing to share information related to the bidi smoking habit were enrolled. A Chi-square test and unpaired t-test were used for the statistical analysis. Results: The base of the tongue was found to be the most common site of oral cancer. It was our observation that 61.75% of men had cancer in the oropharynx, and about 34.8% had cancer in the oral cavity. Conclusion: Bidi smoke is dangerous and contains many carcinogenic agents. Bidi smokers have an increased risk of oropharyngeal cancer as compared to oral cancer.